1997
DOI: 10.1042/bj3280199
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1-induced nuclear factor κB activation is inhibited by overexpression of phospholipid hydroperoxide glutathione peroxidase in a human endothelial cell line

Abstract: Oxygen radicals are commonly accepted mediators in the tumour necrosis factor-mediated nuclear factor κB (NFκB) signalling cascade, but evidence for their role during interleukin-1 (IL-1) signalling is lacking. To test the involvement of hydroperoxides we investigated whether IL-1-induced NFκB activation could be influenced by glutathione peroxidases (GPx). These enzymes remove hydroperoxides with various specificities for the hydroperoxide substrate. By overexpressing phospholipid hydroperoxide glutathione pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(92 citation statements)
references
References 39 publications
(42 reference statements)
2
88
0
2
Order By: Relevance
“…The enzymes such as glutathione S-transferases, aldehyde dehydrogenases, and aldose reductases and transporters such as RalBP1 and MRP1 that catalyze the efflux of its metabolites regulate its intracellular concentrations [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. GSTs catalyze the conjugation of HNE to glutathione (GSH) which is the major pathway for disposition of HNE.…”
Section: Accumulation Of Hne In Cells Lead To Apoptosis-clinical Implmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzymes such as glutathione S-transferases, aldehyde dehydrogenases, and aldose reductases and transporters such as RalBP1 and MRP1 that catalyze the efflux of its metabolites regulate its intracellular concentrations [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. GSTs catalyze the conjugation of HNE to glutathione (GSH) which is the major pathway for disposition of HNE.…”
Section: Accumulation Of Hne In Cells Lead To Apoptosis-clinical Implmentioning
confidence: 99%
“…These studies have opened a new area in the field of ROS-induced signaling focusing on the regulatory roles of the enzymes involved in the formation and metabolism of HNE. Recent studies in this area have shown that enzymes such as glutathione S-transferases (GSTs), aldehyde dehydrogenases, aldose reductase, glutathione peroxidase, and RalBP1 (Ral-binding protein 1) that are among the major determinants of intracellular levels of HNE can modulate stress-induced signaling for programmed cell death [2][3][4][5][6][7][8][9][10]. Some of these studies [11][12][13][14] seem to have major clinical implications particularly in regard to cancer chemotherapy [11,12], inhibition of tumor growth [13], and sepsis [14] as discussed briefly later in this review.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced cysteine residue(s) of NF-B appear to be required for its actual binding to the promotor region of a target gene (11). Dependence of the early activation steps of this cascade on reactive oxygen species is indicated by the inhibitory effects of added N-acetylcysteine and metal chelators (9,10) and increased intracellular levels of phospholipid hydroperoxide glutathione peroxidase (12).…”
mentioning
confidence: 99%
“…It was therefore considered to synergistically act with vitamin E in protecting membranes from lipid peroxidation (9). More recently, however, PHGPx has been implicated in regulating the synthesis of lipid mediators by silencing 5-and 15-lipoxygenase (10 -12), in suppressing hydroperoxideinduced apoptosis (13), in dampening cytokine-induced gene activation (14), in peroxynitrite scavenging (15), and in spermatogenesis (16).…”
mentioning
confidence: 99%